KADERISASI GURU DAN DOKTER GIGI DI NAGARI UJUNG GADING KECAMATAN LEMBAH MELINTANG PASAMAN BARAT - Haria Fitri; Rahmi Khairani Aulia; Novia Wirna Putri (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Dental caries is a major health issue commonly affecting children in Indonesia, including those in Lembah Melintang District, West Pasaman. To support the Indonesia Free of Caries 2030 program, preventive efforts are needed through the training and empowerment of school-level dental health agents, known as "young dentists." This preventive approach aims to establish collective behavior in maintaining dental health and to create a sustainable culture of dental health awareness within schools and the community. The purpose of this training initiative is to enhance teachers’ knowledge and skills in teaching the importance of dental and oral health to students. Furthermore, through the empowerment of young dentists, selected students are trained as health agents to contribute to maintaining dental health at school. The methods used in this program include lectures, interactive discussions, and hands-on practice on oral health maintenance. Results showed an increase in teachers’ understanding of dental and oral health, as well as active student involvement as young dentists fulfilling their roles as health agents. Additionally, an improvement in understanding was observed, reflected in increased scores from pretest to posttest. The conclusion of this activity is that the training of teachers and young dentists can strengthen preventive health measures at schools and support the national goal of Indonesia Free of Caries 2030. This training and empowerment model has proven effective in raising awareness and encouraging community participation in early dental caries prevention.